Efeito Aharonov-Bohm em partículas neutras - Teodoro, Marcio Daldin (Universidade Federal de São Carlos, 2011)
In classical Physics, the motion of an electrically charged particle is affected only by the presence of a magnetic field if the particle enters a region of space in which the field is present. Meanwhile, in quantum Physics, a charged carrier can be affected by the electromagnetic vector potential ~A, even in regions where the magnetic field ~B is not present. This surprising contrast between classical and quantum Physics has been experimentally proven in several beautiful experiments in semiconducting, metallic and superconducting material systems, and has been called Aharonov-Bohm effect. More recently, however, several theoretical works have discussed the plausible existence of this effect even for neutral particles! In this PhD Thesis project it is shown the first clear experimental observation of the Aharonov-Bohm effect in neutral excitons in InAs quantum rings. Signatures of this effect appear as oscillations in the intensity of the photoluminescence emission bands with increasing magnetic fields and also depending on the dimensions of the quantum rings. These oscillations are affected by the uniaxial strain field due to the piezoelectricity of the asymmetric InAs rings, as revealed by the atomic force microscopy, transmission electron microscopy images and X-Ray Diffraction measurements using synchrotron light. A theoretical model that describes the behavior of the excitonic interference pattern and its modulation with temperature and uniaxial electric fields has been used for the interpretation of the experimental data. The detection of AB oscillations mediated by electron-hole pair correlation is a fundamental quantum mechanical effect that will trigger further studies in this area of fundamental physics as well as technological applications.
Keywords: Física da matéria condensada; Aharonov-Bohm, Teoria de; Éxcitons neutros; Magneto-luminescência; Semicondutores; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA::FISICA MATEMATICA